PENGARUH PENGGUNAAN PUPUK NPK RUSTICA YELLOW (15:15:15) DENGAN LAMA WAKTU INDUKSI TERHADAP HASIL TANAMAN BAWANG PUTIH (Allium sativum) - Astri Trinurrani Lolitapitaloka (AGRONISMA, 2021)
Garlic is an agricultural commodity that is much needed as a flavoring agent for several types of food, but the level of availability and fluctuating prices have made farmers reluctant to plant it. Apart from this, the quality of the type or variety of garlic planted and the cultivation method also affects the garlic harvest. One way that can be used to increase the availability of quality garlic is to use the right cultivation technique, namely using SIPLO technology (Local Potential Intensification System). SIPLO is a way to restore nutrient function to the soil by providing electricity to wet or stagnant land to neutralize pH and facilitate the exchange of anions and cations. This study aims to increase the yield of garlic plants. This study used a factorial randomized block design method. Factor 1: SIPLO induction time interval (I0: 0 minutes, I1: 30 minutes, I2: 60 minutes) and factor 2: the concentration of Rustica Yellow fertilizer application (P0: 0 kg / Ha, P1: 200 Kg / Ha, P2: 350 Kg / Ha). The results of this study indicate that in general, the interval (length) of SIPLO induction time and the concentration of Rustica Yellow fertilizer gave good results on garlic plants. Where the SIPLO induction time interval treatment and the concentration of Rustica Yellow fertilizer showed good results in the harvest production of garlic plants